Projecting the impacts of climate change on streamflow in the upper reaches of the Yangtze River basin - Danyang Gao (IWA Publishing, 2021)
The study of climate change impacts on streamflow in small-middle basins within the Upper Yangtze River Basin (UYRB) is not paid enough attention. This paper projected future streamflow changes in the Laixi River basin (LRB), a small-middle basin in the UYRB, during 2041–2100 under RCP2.6, RCP4.5 and RCP8.5 by coupling SDSM and SWAT. The results indicate that the temperature and precipitation in the LRB show a fluctuating upward trend, and the change is most severe under RCP8.5. The increase of maximum temperature is larger than that of minimum temperature. The precipitation changes in May to September are relatively greater than in other months, while temperature is the opposite. More importantly, the streamflow is projected to rise gradually during the whole period. Under RCP2.6, increases of streamflow in the 2050s are greater than in the 2080s, while it is the opposite under RCP4.5 and RCP8.5. The increase in high flow from May to August is expected to be significantly higher than the low flow from September to April. Although the study is focused on the LRB, the results gained can provide a reference for other small-middle basins in the UYRB and all basins experiencing subtropical monsoon humid climate. HIGHLIGHTS It is the first study to project climate impacts on streamflow in the Laixi River basin (LRB).; We do not focus on the whole Upper Yangtze River Basin (UYRB) (1,000,000 km2) but pay attention to a small-middle basin (3,240 km2) within it.; We focus on streamflow response in a subtropical monsoon humid climate basin.; This paper coupled SDSM and SWAT.; Comparative analysis of differences between the LRB and the UYRB were discussed.;